The association between midwifery staffing levels and the experiences of mothers on postnatal wards: Cross sectional analysis of routine data. Issue 6 (November 2022) - Turner, L.; Culliford, D.; Ball, J.; Kitson-Reynolds, E.; Griffiths, P.
Abstract: Background: Women have consistently reported lower satisfaction with postnatal care compared with antenatal and labour care. The aim of this research was to examine whether women's experience of inpatient postnatal care in England is associated with variation in midwifery staffing levels. Methods: Analysis of data from the National Maternity Survey in 2018 including 17, 611 women from 129 organisations. This was linked to hospital midwifery staffing numbers from the National Health Service (NHS) Workforce Statistics and the number of births from Hospital Episode Statistics. A two-level logistic regression model was created to examine the association of midwifery staffing levels and experiences in post-natal care. Results: The median Full Time Equivalent midwives per 100 births was 3.55 (interquartile range 3.26–3.78). Higher staffing levels were associated with less likelihood of women reporting delay in discharge (adjusted odds ratio [aOR] 0.849, 95% CI 0.753–0.959, p = 0.008), increased chances of women reporting that staff always helped in a reasonable time aOR1.200 (95% CI 1.052, 1.369, p = 0.007) and that they always had the information or explanations they needed aOR 1.150 (95% CI 1.040, 1.271, p = 0.006). Women were more likely to report being treated with kindness and understanding with higher staffing, but the difference was small and not statistically significant aOR 1.059 (0.949, 1.181, p = 0.306). Conclusions: Negative experiences for women on postnatal wards were more likely to occur in trusts with fewer midwives. Low staffing could be contributing to discharge delays and lack of support and information, which may in turn have implications for longer term outcomes for maternal and infant wellbeing.